The Meaning of Traditional Graduation in Lekuk 50 Tumbi Lempur Community, Kerinci Regency, Jambi Province - Yolla Ramdani; Astrid Qommanecci (Mudra Jurnal Seni Budaya, 2020)
This article is the result of research conducted aiming to find out the meaning of customary graduation tradition that is still being carried out by Lekuk 50 Tumbi Lempur community until now. This traditional graduation is being held by Depati Nan Sepuluh (The Ten Leaders) to give titles to the sons and daughters of Lekuk 50 Tumbi Lempur community who have already obtained educational degree e.g. bachelor degree, master’s degree, and doctoral degrees. They celebrate this every year on 2 Shawwal or coinciding with Eid al-Fitr at some specified Village Hall. This research uses descriptive qualitative method where data was collected through observation, interview and documentation study. Result shows that series of activity process are being done for the inauguration procession. Bachelor’s degree holders will be confirmed as Cendikionegaro, while Master’s degree holders as Cendikionegaro Pertamo and Post Graduates degree holders/Professors as Cendikionegaro Utama. From the results of this study, it can be seen that the tradition of this customary graduation has a special meaning for the society of Lekuk 50 Tumbi Lempur as a form of appreciation given by The Ten Leaders so that the sons and daughters of Lempur is honoured and proud of their achievements. In addition to the achievements and degrees that they obtained, it was also a form of recognition of their degree in the society. This customary title is expected to motivate the sons and daughters of Lekuk 50 Tumbi Lempur to reach their goals and achieve success in the future.